Management of an enlarging aortic aneurysm in the presence of radiation induced retroperitoneal fibrosis. - Todd, G J; Schwartz, A; Rapoport, F (J Cardiovasc Surg (Torino), 1989)
Despite a thoracoabdominal retroperitoneal approach to an enlarging symptomatic infrarenal aortic aneurysm, proximal aortic dissection was hazardous due to radiation induced retroperitoneal fibrosis. Iliac artery ligation and thoracic aorta to iliac artery bypass has resulted in successful management during 14 months of follow-up.
Keywords: Aged; Aorta, Abdominal; Aortic Aneurysm; Blood Vessel Prosthesis; HUMANS; Lymphoma; Male; Radiation Injuries; Retroperitoneal Fibrosis; Retroperitoneal Neoplasms; T-Lymphocytes